Time-resolved gas thermometry by Laser Induced Grating Spectroscopy with a high-repetition rate laser system - Förster, F; Crua, C; Davy, M; Ewart, P (Springer Verlag, 2017)
Thermometry using Laser Induced Grating Spectroscopy (LIGS) is reported using a high– repetition rate laser system, extending the technique to allow time–resolved measurements of gas dynamics. LIGS signals were generated using the second harmonic output at 532 nm of a commercially available high– repetition rate Nd:YAG laser with nitrogen dioxide as molecular seed. Measurements at rates up to 10 kHz were demonstrated under static cell conditions. Transient temperature changes of the same gas contained in a cell subjected to rapid compression by injection of gas were recorded at 1 kHz to derive the temperature evolution of the compressed gas showing temperature changes of 50 K on a time scale of 0.1 s with a measurement precision of 1.4 %. The data showed good agreement with an analytical thermodynamic model of the compression process.